Solvent Effect on Acrylamide with Methylmethacrylate and Ethylmethacrylate Copolymer-Synthesis and Characterization - Sreenivasulu, B.; Raghunatha Rao, P. (Asian Journal of Chemistry, 2012)
Free radical copolymerisation of acrylamide (A) with methyl methacrylate (MM) and ethylmethacrylate (EM) have been carried out using 2,2'-azo-bis-isobutyronitrile (AIBN) at 60 ºC using dimethyl formamide (DMF), dimethyl sulfoxide (DMSO) and dioxane as solvents. The copolymers AMM and AEM were characterized by IR and 1H NMR studied. The reactivity ratios (r) of the copolymers were determined by YBR method. The effect of solvent on these copolymerizations has been discussed.